Extended Release Liposomal Bupivacaine Injection (Exparel) for Early Postoperative Pain Control Following Palatoplasty. Issue 5 (July 2018) - Day, Kristopher M.; Nair, Narayanan M.; Sargent, Larry A.
Abstract : Introduction: Liposomal bupivacaine (LB) is a long-acting local anesthetic reported to decrease postoperative pain in adults. The authors demonstrate the safe use of LB in pediatric patients with improved pain control following palatoplasty. Materials and Methods: Retrospective patient series of all single-surgeon palatoplasty patients treated at a tertiary craniofacial center from August 2014 to December 2015 were included. All patients received 1.3% LB intraoperatively as greater palatal nerve and surgical field blocks in 2-flap V–Y pushback palatoplasty. Postoperative oral intake, opioids administered, duration of hospitalization, and FLACC (face, legs, activity, cry, consolability) pain scores were measured. Results: Twenty-seven patients (16 males and 11 females, average age of 10.8 months, weight 8.8 kg) received 2.9 ± 0.9 mL (2.6 ± 1.9 mg/kg) 1.3% LB. Average FLACC scores were 2.4 ± 2.2/10 in the postanesthesia care unit and 3.8 ± 1.8/10 while inpatients. Oral intake was first tolerated 10.3 ± 11.5 hours postoperatively and tolerated 496.4 ± 354.2 mL orally in the first 24 hours postoperatively. Patients received 8.5 ± 8.4 mg hydrocodone equivalents (0.46 ± 0.45 mg/kg per d hydrocodone equivalents) and were discharged 2.1 ± 1.3 days postoperatively. Opioid-related adverse events included emesis in 7.4% and pruritis in 3.7% of patients. Conclusions: The LB may be used safely in pediatric patients. Intraoperative injection of LB during palatoplasty can yield low postoperative opioid use and an early and adequate volume of oral intake over an average hospital stay. Further cost-efficacy studies of LB are needed to assess its value in pediatric plastic surgery.